The Study of Language THIRD EDITION - Yule, George (Cambridge University, 2013)
This revised and updated edition incorporates many changes that reflect developments in language study over the past decade. There is an entirely new chapter on pragmatics, with an expansion of the chapter on semantics. The explosion of interest in many of the 'applied' areas of language study is also reflected in additional sections on speech recognition systems, sign languages, women's and men's language, input in language learning, and several other topics. The Study Questions and Discussion Topics have also been thoroughly revised; and the Further Reading sections have been revised, updated and expanded. --From publisher's description.